Effect of Bulbous Bow on Ice Resistance of Ice Ship - Afrizal, Efi; Koto, J; M.A, Wahid (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Ice resistance is very important in design of an ice ship due to related to the propulsion system. Bulbous bow ship economically has advantage during sailing in open water due to lower resistance compared with an ice bow. On the other hand, the bulbous bow ship has higher ice resistance due to bulbous bow. This paper discusses effect of bulbous bow on ice resistance of ice ship using Finite Element Method. In the simulation, the interaction of bulbous bow-ice was detected using the Couple Eulerian Langrangian. Simulation was run at ship speeds of 0.4 m/sand 0.5 m/s at 0.5 m of ice thickness. It was founded that during ice crushing, the pressure changes that occur in the hull are directly combined with changes in the internal energy of the ice. The ice resistance increases due to buckling and bending created by bulbous bow.